PWE-092 CT pneumocolon in a district general hospital – is this test being used appropriately?. (23rd September 2015) - Sarai, P; Sebepos-Rogers, G; Mann, S D
Abstract : Introduction: CT pneumocolon (virtual colonoscopy, VC) is increasingly being used to investigate the colon in patients who would previously have had a barium enema or optical colonoscopy (OC). It is not associated with sedation complications and is rapid and relatively safe. Unlike OC, published guidelines for appropriate use and reporting standards for VC are scarce.1 We aimed to review the indications and the quality of VC reports in a single centre in the UK. Methods: All patients investigated with VC at Barnet Hospital during a 12-month period from Jan to Dec 2008 were identified from the Radiology Department database. Demographic data, referral source, clinical indications, report details and findings were analysed. Results: 355 patients had VC in 2008 (M=149; age range 29–96 years; mean 74.2 years). Out-patients represented 94% of requests (n=335). 75.8% were referred from GI surgeons, 11.8% from gastroenterologists and 8.4% from Elderly Care Medicine. 20 patients (6%) had VC as in-patients. The most common indications for VC were abdominal pain (23%), anaemia (17%) and weight loss (16%). Incomplete OC was the indication in 13% of requests and frailty in 1% of requests. Among in-patients, anaemia was the indication in 60% and frailty in 5%. The reports documented the procedure as suboptimal in 10% of requests even though poor prep was highlighted in 27% of cases (no faecal tagging used). Reference to the adequacy of distension and the use of anti-spasmodics were made in 61% and 30% of reports, respectively. The findings were similar for in-patients and out-patients, although more inpatients had poor prep (50%). There were no adverse events following VC. Normal or incidental benign observations (diverticular disease, gallstones, etc) were reported in 78.5% of out-patients. Polyps or cancer were found in 10% and another 4% had significant extra-colonic pathology. Conclusion: The overwhelming majority of requests for VC are made by GI surgeons. The indications are varied and only 14% of out-patient procedures were for commonly accepted indications (frailty and incomplete OC). The quality of reporting detail varied with poor prep being identified in over one in four cases. Abdominal pain is associated with a poor yield from VC. Units that perform VC should establish guidelines for appropriate use. Like OC, we propose that VC is a specialist GI investigation which should be interpreted and reported by dedicated GI radiologists with a minimum recommended reporting standard.